Lecture Building Planning FKIP UNMUL Banggeris Campus In Samarinda Emphasis On Artificial Lighting (International Journal of Architecture and Urbanism, 2024)
The design of the FKIP UNMUL Lecture Building on the Banggeris Samarinda Campus with an emphasis on artificial lighting is an effort to create an optimal learning environment for students and lecturers. Artificial lighting is the main focus in this design, taking into account aspects of energy efficiency, health and visual comfort. Through a holistic design approach, this lecture building is expected to be able to optimally integrate natural and artificial lighting concepts. Apart from that, it also considers aesthetic aspects and environmental sustainability. This design aims to create an inspiring and comfortable learning space for building users, while reducing inefficient energy consumption. Thus, it is hoped that this design can be an example for other lecture buildings in utilizing artificial lighting effectively.